Preliminary evaluation of the effect of dietary supplementation of Bacillus clausii for adult healthy cats - Alessio Ruggiero; Giorgia Meineri; Alessandro Vastolo; Raffaella Adami; Nicolò Lonigro; Monica Isabella Cutrignelli (Italian Journal of Animal Science)
This study examines the influence of Bacillus clausii supplementation on feline nutrition, addressing the growing interest among pet owners in improving their pets’ health and well-being through probiotics. As companion animals are increasingly regarded as members of the family, there is a growing emphasis on their dietary and health-related considerations. The objective of this study is to investigate the impact of Bacillus clausii, a strain with established antimicrobial and immunomodulatory properties, on the gut health of cats. A total of 14 neutered Chartreux cats were recruited for a double-blind trial. The cats were divided into two groups: a control group and a treatment group. The treatment group received Bacillus clausii supplements in their diet. Over 42 days, the body weight (BW), Body Condition Score (BCS) and faecal quality of the subjects were monitored. The results indicated a significant increase in feed intake in the treatment group in comparison to the control group, which suggests an improvement in digestive health. No significant differences in BW and BCS were discerned. Furthermore, the treatment group showed improved stool quality, reduced faecal scores and high dry matter content. IgA level increased in the faeces and reduced levels of calprotectin, a marker of intestinal inflammation, in the treatment group indicated better gut health. Bacillus clausii administration also resulted in an increase in short-chain fatty acids and butyrate, which promoted a beneficial microbial population. These preliminary results suggest that Bacillus clausii supplementation may improve gut health in cats, potentially leading to better health and well-being.